American Street - Zoboi, Ibi Aanu (Balzer + Bray, an imprint of HarperCollins Publishers, 2017)
When Fabiola's mother is detained upon their arrival to the United States, Fabiola must navigate her loud American cousins, the grittiness of Detroit's west side, a new school, and a surprising romance all on her own.